Francisco Suarez and Mathematics. Remarks on its Scientific Character according to Disputationes Metaphysicae I - Felipe Mendoza, José María (2021)
The present work proposes a brief introduction to the mathematical doctrine of Francisco Suarez according to his Disputationes Metaphysicae I. The context of his researching deals with the notion of obiectum aedecuatum, a theory of abstraction and the order of sciences in general terms. Therefore, in order to better understanding the mathematical sciences, it´s necessary to observe its relationship with metaphysics and define the ground and the limits of mathematical philosophy.